1996
DOI: 10.1016/0014-5793(96)01067-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sub‐optimal protein nutrition on insulin hypersecretion evoked by high‐energy/high‐fat feeding in rats

Abstract: Low (8%) protein feeding during pregnancy impairs the functional development of the fetal endocrine pancreas. ('ontinued low-protein feeding post-nataHy decreases pancreatic insulin content and secretion, whereas transfer to standard diet evoked ~-cell recuperation. Glncose-stimulated insulin secretion (GSIS) and insulin action were examined in vivo at 28 days after transfer from 8% protein diet to a high-energy/high-fat/standard (20%)-protein diet (HEF diet). HEF feeding dramatically enhanced GSIS after intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…The total and saturated fat content of our Lard diet lies at the upper end of the typical fat intake for people in the U.S. (32)(33)(34), whereas the fat intake in the Surwit diet exceeds that normally consumed by humans and may elicit greater lipotoxicity within the ␤-cell. More importantly, the diets in the current study, and that reported by Holness and Sugden (28,30), provide significant amounts of carbohydrates in the form of complex carbohydrates, whereas the diabetogenic Surwit diet contains only the simple sugars maltose and sucrose. Therefore, it is quite likely that an interaction with the carbohydrate component of the diet modifies the impact of fat intake on GSIS.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The total and saturated fat content of our Lard diet lies at the upper end of the typical fat intake for people in the U.S. (32)(33)(34), whereas the fat intake in the Surwit diet exceeds that normally consumed by humans and may elicit greater lipotoxicity within the ␤-cell. More importantly, the diets in the current study, and that reported by Holness and Sugden (28,30), provide significant amounts of carbohydrates in the form of complex carbohydrates, whereas the diabetogenic Surwit diet contains only the simple sugars maltose and sucrose. Therefore, it is quite likely that an interaction with the carbohydrate component of the diet modifies the impact of fat intake on GSIS.…”
Section: Discussionmentioning
confidence: 49%
“…In particular, Holness and Sugden (28,30) showed that the provision of rats with dietary saturated fat significantly enhanced insulin secretion during an intravenous glucose challenge. Ahren et al (31) examined responses in rats receiving a diet supplemented with 58% of calories from lard.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic studies among humans and in particular among rodents have shown permanent changes in the structure and/or function of involved organs after exposure to an adverse intrauterine environment during critical stages of foetal development leading to the development of two major metabolic abnormalities responsible for the development of overt Type II diabetes i.e. impaired insulin secretion [7,8,9,10,11,12] and insulin resistance [13,14,15,16,17,18,19]. However, most human studies have used indirect techniques to measure insulin action including hyperinsulinaemia, HOMA or insulin sensitivity index (MINMOD) [13,14,15,18], and several studies have failed to show Several epidemiological studies have indicated an influence of the intrauterine environment and in particular of low birth weight for the development of Type II (non-insulin-dependent) diabetes mellitus later in life [1][2][3][4][5].…”
mentioning
confidence: 99%
“…However, these offspring undergo a greater age-dependent loss of glucose tolerance compared to controls such that by 15 months of age these animals have a significantly worse glucose tolerance than controls (9). There are also data to suggest that this deterioration can be accelerated by the provision of a high-fat diet (19 (12). These changes appeared to be associated with an increased hepatic glucose output (20).…”
mentioning
confidence: 99%
“…Interestingly, the growth of the spontaneously hypertensive rat (SHR) is reduced at days [16][17][18][19][20] but is normal at birth. Growth retardation is associated with a placenta larger than normal (58).…”
mentioning
confidence: 99%